Las regalías contractuales como mecanismo alternativo de financiamiento de la industria minera - Rafael (2021)
With a mining ecosystem in constant evolution, contractual royalties have emerged as a new financing method for projects that require millionaire investments. The author analyzes the operation and applicability of this method, recently introduced in Peru, and how it fits into the national legal system. In order to do this, he first analyzes the nature of the contractual royalty and how it is regulated by our legal system, to then study the different types that emerge in practice and their content.